Implementasi Prinsip Ekonomi Para Produsen Anyaman Ketupat di Desa Joanyar - Santi, Ni Wayan Ayu; Indrayani, Luh (Ekuitas: Jurnal Pendidikan Ekonomi, 2023)
The aim of this research is to determine the implementation of economic principles for ketupat woven producers in Joanyar Village. The type of research used is descriptive qualitative research. This research uses data collection techniques in the form of observation and interviews. Observation activities include systematic recording of events, behavior, objects seen and other things needed to support the research being carried out. Interviews in this research were conducted with fifteen informants to ask questions regarding the implementation of economic principles by ketupat woven producers. Data was analyzed through three stages, namely data reduction, data presentation, drawing conclusions. The results of this research concluded that the economic principles that have been implemented by ketupat woven producers include sacrificing costs needed to get something, rational thinking, the market as a place for economic activities, and trade that benefits all parties. Implementing economic principles provides greater profits or results so that ketupat woven producers are able to use the profits to meet their daily needs.